A terpene polysulfide oligomer / polyacrylonitrile composite material and its preparation and application
By preparing terpene polysulfur oligomer and polyacrylonitrile composite materials as the positive electrode material of lithium sulfur batteries, the problems of loss of active components and reduced Coulomb efficiency during the charging and discharge process of lithium sulfur batteries are solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202310071881.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-02-07
AI Technical Summary
Lithium sulfur batteries form soluble lithium polysulfide intermediates during the charge and discharge reaction, resulting in loss of active components, rapid attenuation of capacity and reduction of Coulomb efficiency during the battery cycle.
By preparing a composite material of terpene polysulfur oligomer and polyacrylonitrile, the composite material formed is used as the positive electrode material of lithium sulfur battery, reducing the generation of long-chain polysulfides and improving the conductivity of the positive electrode.
It significantly improves the cycle stability and energy density of lithium-sulfur batteries, improves the safety performance of lithium-sulfur batteries, and reduces the occurrence of "shuttle effect".
Smart Images

Figure CN116284516B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium-sulfur battery materials, and specifically relates to a terpene polysulfide oligomer / polyacrylonitrile composite material and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries (LIBs) have been widely used in portable consumer electronics and mobile power supplies. However, with the development of electric vehicles and distributed energy storage, traditional lithium-ion battery systems based on intercalation chemistry (such as LiCoO2|graphite batteries) can no longer meet their needs for high energy density, long cycle and low energy storage cost. In the process of developing a new generation of energy storage technology, lithium-sulfur (Li-S) batteries based on multi-electron conversion reactions have become a very important research content and direction in the current electrochemical energy storage field due to their ultra-high energy density, low material price and excellent environmental friendliness. Especially in the research and development of new energy vehicles, due to the limitation of the energy density of traditional lithium-ion batteries, their performance is often unsatisfactory. Developing batteries with higher energy density to meet the growing living needs of future society is not only a challenge faced by countries around the world, but also a general trend.
[0003] Compared with lithium-ion batteries, lithium-sulfur battery systems have attracted great interest from researchers due to their rich sulfur reserves, ultra-high theoretical capacity and environmentally friendly characteristics. The internal structure of lithium-sulfur batteries is mainly composed of metallic lithium as the negative electrode and elemental sulfur as the positive electrode active material. During the discharge process, metallic lithium loses electrons and becomes lithium ions, which migrate to the positive electrode through the electrolyte and react with elemental sulfur. As the discharge proceeds, the product gradually transforms from lithium polysulfide to lithium sulfide; during the charging process, lithium sulfide undergoes electrochemical oxidation, thereby releasing lithium ions and converting into elemental sulfur, and lithium ions migrate back to the negative electrode and deposit as metallic lithium. Due to the ultra-high theoretical capacity of the active material (lithium: 3800mAh / g; sulfur: 1675mAh / g), the assembled lithium-sulfur battery has a theoretical energy density of up to 2600Wh / kg, and is considered to be the first choice for the next generation of high-energy-density lithium batteries. However, the inherent defects of lithium-sulfur batteries themselves have hindered their further development and commercial application. To achieve high-performance and long-life lithium-sulfur batteries, the most important thing is to overcome the following two points: First, soluble lithium polysulfide (LiPS) intermediates are formed during the charge and discharge reaction, and shuttle between the positive and negative electrodes to form a "shuttle effect", resulting in the loss of active components, rapid capacity decay and reduced coulombic efficiency during the battery cycle; Second, the charge and discharge products of the positive electrode active material S / Li2S are both electronic and ion insulators, resulting in low active material utilization and poor rate performance when used as a positive electrode material. Summary of the invention
[0004] In view of the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a terpene polysulfide oligomer / polyacrylonitrile composite material.
[0005] Another object of the present invention is to provide a terpene polysulfide oligomer / polyacrylonitrile composite material prepared by the above method.
[0006] Another object of the present invention is to provide an application of the above-mentioned terpene polysulfide oligomer / polyacrylonitrile composite material.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a terpene polysulfide oligomer / polyacrylonitrile composite material comprises the following steps:
[0009] (1) After heating sulfur to 155-175° C., a terpene compound is added thereto, and the reaction is continued at 155-175° C. for 5-6 hours to obtain terpene polysulfide oligomers (PST);
[0010] (2) Activating polyacrylonitrile at 400-500° C. for 3-4 hours to obtain activated polyacrylonitrile (PAN);
[0011] (3) The terpene polysulfide oligomer is mixed with activated polyacrylonitrile, a Lewis acid catalyst is added to the mixture, and then the mixture is calcined at a high temperature to obtain a terpene polysulfide oligomer / polyacrylonitrile composite material.
[0012] Furthermore, in step (1), the mass ratio of sulfur to terpene compound is (2-3):1.
[0013] Furthermore, the terpene compound is at least one of D-limonene, α-pinene or β-pinene.
[0014] Furthermore, both step (1) and step (2) are carried out under nitrogen or inert gas atmosphere.
[0015] Furthermore, the molecular weight of the polyacrylonitrile is 140,000 to 150,000, and the average particle size of the activated polyacrylonitrile is 8 to 10 um.
[0016] Furthermore, in step (3), the mass ratio of terpene polysulfide oligomer to activated polyacrylonitrile is (4-5):1, and the mixing is specifically carried out at 155-175° C. for 2-3 hours.
[0017] Furthermore, the Lewis acid catalyst is at least one of AlCl3, SbCl5, FeCl3, SnCl4, TiCl4, ZnCl2, BF3, and FeBr3.
[0018] Furthermore, the amount of the Lewis acid catalyst added is 1-2% of the amount of the reaction substrate.
[0019] Furthermore, the high-temperature calcination in step (3) is carried out in a nitrogen or inert gas atmosphere, the calcination temperature is 300-500° C., and the calcination time is 4-5 hours.
[0020] The terpene polysulfide oligomer / polyacrylonitrile composite material prepared by the invention can be used as a positive electrode material for lithium-sulfur batteries.
[0021] The principle of the present invention is that the reaction of sulfur with terpene substances can not only change the long-chain state of sulfur into a short-chain state, but also a large number of thiol active functional groups exist at the end of the reaction product terpene polysulfide oligomer. The thiol and polyacrylonitrile are stably combined by utilizing the organic reaction of the thiol and polyacrylonitrile. In the structure of the obtained terpene polysulfide oligomer / polyacrylonitrile (PST-PAN), the long chain of sulfur is changed into a short chain of polysulfide oligomer, and the long-chain polysulfide is reduced or even not generated during the discharge process of the battery to inhibit the generation of the "shuttle effect"; the carbon skeleton of polyacrylonitrile after high-temperature treatment is a good conductor, and the introduction of the porous structure of polyacrylonitrile after high-temperature activation enhances the conductivity of the positive electrode.
[0022] Compared with the prior art, the present invention achieves the following technical effects:
[0023] (1) The present invention first prepares terpene polysulfide oligomers and activated polyacrylonitrile respectively through chemical and physical treatments, and then uniformly compounds the terpene polysulfide oligomers and polyacrylonitrile through a click reaction (the thiol groups on the terpene polysulfide oligomers and the unsaturated bonds on the polyacrylonitrile are compounded through chemical bonding). The prepared terpene polysulfide oligomer / polyacrylonitrile composite material is used as a positive electrode for a lithium-sulfur battery, which can take into account both inhibiting the "shuttle effect" of long-chain polysulfides and improving the electrochemical reaction kinetics of the positive electrode, and on this basis significantly improves the cycle stability and energy density of the lithium-sulfur battery, thereby improving the safety performance of the lithium-sulfur battery.
[0024] (2) The terpene polysulfide oligomer / polyacrylonitrile composite material of the present invention can be widely used in lithium-sulfur batteries, especially in the field of power lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1This is a SEM image of the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in Example 1 of the present invention.
[0027] Figure 2 This is the EDS energy spectrum of the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in Example 1 of the present invention.
[0028] Figure 3 Cyclic voltammetry curve (scan rate of 0.1 mV / S) obtained by assembling a CR2032 button cell using the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in Example 1 of the present invention as the positive electrode, lithium metal as the negative electrode, Celgard 2400 as the separator, and 1% mass concentration of LiNO3 dissolved in a solution of distilled dimethoxyethane:1,3-dioxolane (v / v=1:1) using 1M bis(trifluoromethanesulfonyl)imide lithium salt as the electrolyte to form a CR2032 button cell.
[0029] Figure 4 The 0.1C 200 cycle data was measured for a CR2032 button battery assembled with the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in Example 1 of the present invention as the positive electrode, lithium metal as the negative electrode, Celgard 2400 as the separator, and 1% mass concentration of LiNO3 dissolved in a solution of distilled dimethoxyethane:1,3-dioxolane (v / v=1:1) of 1M bis(trifluoromethanesulfonyl)imide lithium salt as the electrolyte. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work should fall within the scope of protection of the present invention.
[0031] Unless otherwise specified, the technical solutions described in the present invention are all conventional technologies in the art.
[0032] Example 1
[0033] (1) Add 24 g of sulfur into a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 8 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0034] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0035] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 300° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0036] The SEM image of the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in this example is as follows: Figure 1 As shown, it can be clearly observed that its surface morphology is a uniform spherical shape.
[0037] The EDS spectrum of the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in this example is as follows: Figure 2 As shown, it can be clearly observed that the S element is uniformly distributed in the prepared composite material.
[0038] The terpene polysulfide oligomer / polyacrylonitrile composite material prepared in this embodiment is used as the positive electrode, lithium metal is used as the negative electrode, Celgard2400 is used as the separator, and 1% mass concentration of LiNO3 is dissolved in a solution of distilled dimethoxyethane:1,3-dioxolane (v / v=1:1) with 1M bis(trifluoromethanesulfonyl)imide lithium salt as the electrolyte, and a CR2032 button cell is assembled and tested at a scan rate of 0.1mV / S to obtain a CV curve as shown in FIG. Figure 3 The four curves in the figure are the first cycle of 0.1C cycle discharge, the tenth cycle of 0.1C cycle discharge, the fiftieth cycle of 0.1C cycle discharge and the hundredth cycle of 0.1C cycle discharge. From the CV curve, it can be seen that even in the hundredth cycle, two reduction peaks were not observed during the discharge process, which indicates that the conversion process of long-chain polysulfides to short-chain polysulfides did not occur during the discharge process corresponding to lithium sulfur, reducing the generation of polysulfides or even eliminating the generation of polysulfides.
[0039] The terpene polysulfide oligomer / polyacrylonitrile composite material prepared in this embodiment is used as the positive electrode, lithium metal is used as the negative electrode, Celgard2400 is used as the separator, and 1% mass concentration of LiNO3 is dissolved in a solution of distilled dimethoxyethane:1,3-dioxolane (v / v=1:1) with 1M bis(trifluoromethanesulfonyl)imide lithium salt as the electrolyte, and assembled into a CR2032 button battery for testing to obtain 0.1C 200 cycle data as shown in the following figure: Figure 4As shown in the figure, the attenuation rate of the battery per cycle in the 200-cycle cycle data is very small (less than 0.4%), which shows that the terpene polysulfide oligomer / polyacrylonitrile composite material prepared in this example has a significant effect in inhibiting the generation of polysulfides as a positive electrode of a lithium-sulfur battery.
[0040] Example 2
[0041] (1) Add 24 g of sulfur into a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 8 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0042] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0043] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 350° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0044] Example 3
[0045] (1) Add 24 g of sulfur into a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 8 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0046] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0047] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 400° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0048] Example 4
[0049] (1) Add 24 g of sulfur into a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 8 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0050] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0051] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 450° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0052] Example 5
[0053] (1) Add 24 g of sulfur into a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 8 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0054] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0055] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 500° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0056] Example 6
[0057] (1) Add 21 g of sulfur to a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 9 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0058] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0059] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 300° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0060] Example 7
[0061] (1) Add 21 g of sulfur to a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 9 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0062] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0063] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 350° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0064] Example 8
[0065] (1) Add 21 g of sulfur to a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 9 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0066] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0067] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 400° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0068] Example 9
[0069] (1) Add 21 g of sulfur to a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 9 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0070] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0071] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 450° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0072] Example 10
[0073] (1) Add 21 g of sulfur to a three-necked flask and heat it to 155°C under nitrogen protection. When the sulfur changes from solid to liquid, slowly drip 9 g of D-limonene in a constant pressure funnel into the three-necked flask. Raise the temperature to 175°C and react for 6 hours. The resulting clear brick-red solution is terpene polysulfide oligomer (PST).
[0074] (2) Weigh 8 g of dried polyacrylonitrile (molecular weight of about 150,000) and activate it in a tube furnace filled with Ar at 400° C. for 4 h to obtain activated polyacrylonitrile (PAN) with an average particle size of 8 to 10 μm.
[0075] (3) Add 8 g of the terpene polysulfide oligomer prepared in step (1) into a three-necked flask. When the temperature rises to 155° C., add 2 g of the activated polyacrylonitrile prepared in step (2) and mix for 2 h. Then, add 0.1 g of AlCl3 and transfer the mixture to a tubular furnace filled with Ar atmosphere and calcine at 500° C. for 4 h to obtain a black block-shaped porous terpene polysulfide oligomer / polyacrylonitrile composite material.
[0076] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a terpene polysulfide oligomer / polyacrylonitrile composite material, characterized in that: The following steps are involved: (1) After heating sulfur to 155-175° C., a terpene compound is added thereto, and the reaction is continued at 155-175° C. for 5-6 hours to obtain a terpene polysulfide oligomer; the terpene compound is D-limonene; (2) Activating polyacrylonitrile at 400-500°C for 3-4 hours to obtain activated polyacrylonitrile; (3) The terpene polysulfide oligomer is mixed with activated polyacrylonitrile, a Lewis acid catalyst is added to the mixture, and then the mixture is calcined at a high temperature to obtain a terpene polysulfide oligomer / polyacrylonitrile composite material.
2. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: The mass ratio of sulfur to terpenoid compound in step (1) is (2-3):
1.
3. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: Both step (1) and step (2) are carried out under nitrogen or inert gas atmosphere.
4. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: The molecular weight of the polyacrylonitrile is 140,000-150,000, and the average particle size of the activated polyacrylonitrile is 8-10 μm.
5. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: In step (3), the mass ratio of terpene polysulfide oligomer to activated polyacrylonitrile is (4-5):1, and the mixing is specifically carried out at 155-175° C. for 2-3 h.
6. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: The Lewis acid catalyst is at least one of AlCl3, SbCl5, FeCl3, SnCl4, TiCl4, ZnCl2, BF3, and FeBr3; the added amount of the Lewis acid catalyst is 1-2% of the mass of the reaction substrate.
7. The method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 1, characterized in that: The high-temperature calcination in step (3) is carried out in a nitrogen or inert gas atmosphere, the calcination temperature is 300-500° C., and the calcination time is 4-5 h.
8. The terpene polysulfide oligomer / polyacrylonitrile composite material prepared by the method for preparing the terpene polysulfide oligomer / polyacrylonitrile composite material according to any one of claims 1 to 7.
9. Use of the terpene polysulfide oligomer / polyacrylonitrile composite material according to claim 8 in a lithium-sulfur battery.
Citation Information
Patent Citations
Preparation method and application of high-sulfur-loading high-conductivity vulcanized polyacrylonitrile
CN115160465A
Vulcanized polyacrylonitrile material, lithium-sulfur battery positive electrode thereof and lithium-sulfur battery
CN115304797A